The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5581/1516-8484.20120078
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal transcranial Döppler ultrasonography in children with sickle cell disease

Abstract: Background Stroke is a potentially fatal complication of sickle cell disease in children between 2-16 years and transcranial Döppler has been recommended as a screening method in these cases. Objective The main goal of this study was to correlate transcranial Döppler results to complications related to stroke in sickle cell disease and baseline characteristics of the population. Methods This was an observational study of children and adolescents with ages between 2-16 years with sickle cell disease who were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(23 reference statements)
1
13
1
1
Order By: Relevance
“…In the STOP trial, the prevalence was 9·3% (Adams et al , ) and this proportion did not vary among 14 geographical sites in the US and one in Canada. Our frequency of TCD velocities was higher than those reported from Brazil (4·0%) (Leite et al , ) and Nigeria (4·7%) (Lagunju et al , ), but lower than that recorded in Mali (8·1%) (Dorie et al , ). Although the rate of abnormal TCD velocities was higher in Jamaica than Nigeria, the rate of conditional velocities was lower than in Nigeria, which was 25·3% (Lagunju et al , ).…”
Section: Discussioncontrasting
confidence: 68%
“…In the STOP trial, the prevalence was 9·3% (Adams et al , ) and this proportion did not vary among 14 geographical sites in the US and one in Canada. Our frequency of TCD velocities was higher than those reported from Brazil (4·0%) (Leite et al , ) and Nigeria (4·7%) (Lagunju et al , ), but lower than that recorded in Mali (8·1%) (Dorie et al , ). Although the rate of abnormal TCD velocities was higher in Jamaica than Nigeria, the rate of conditional velocities was lower than in Nigeria, which was 25·3% (Lagunju et al , ).…”
Section: Discussioncontrasting
confidence: 68%
“…Accordingly, these children presented more pronounced anemia than those with lower TAMMV. Some authors have reported that anemia may pose an additional risk of stroke development in SCA individuals [ 7 , 13 , 25 ]. It has also been suggested that the increased cerebral blood flow and flow velocity associated with chronic anemia can cause disturbances in blood flow, which may lead to cerebrovascular damage [ 7 , 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table shows reported transcranial Doppler values from the United States, France, Brazil, Tanzania, Nigeria, and Iran in which the proportions with abnormal values ranged from 1.6% to 20.7%. However, the 2 studies from the Arabian Peninsula (Oman and Kuwait) did not record any abnormal values, whereas the study from Iran reported 3% .…”
Section: Classification Of Tammv Values Reported From Different Countmentioning
confidence: 99%